Bilateral lesion of the cerebellar fastigial nucleus: Effects on smooth pursuit acceleration and non-reflexive visually-guided saccades - Helmchen, Christoph; Machner, Björn; Schwenke, Hannes; Sprenger, Andreas (Frontiers in Neurology, 2022)
ABSTRACT Background „Central dizziness“ due to acute bilateral midline cerebellar disease sparing the posterior vermis has specific oculomotor signs. The oculomotor region of the cerebellar fastigial nucleus (FOR) crucially controls the accuracy of horizontal visually-guided saccades and smooth pursuit eye movements. Bilateral FOR lesions elicit bilateral saccade hypermetria with preserved pursuit. It is unknown whether the initial acceleration of smooth pursuit is impaired in patients with bilateral FOR lesion. Objective We studied the effect of a cerebellar lesion affecting the deep cerebellar nuclei on the initial horizontal pursuit acceleration and investigated whether saccade dysmetria also affects other types of volitional saccades, i.e. memory-guided saccades and anti-saccades, which are not performed in immediate response towards the visual target. Methods We recorded eye movements during a sinusoidal and step-ramp target motion paradigm as well as visually-guided saccades, memory-guided saccades and anti-saccades in one patient with a circumscribed cerebellar hemorrhage and 18 healthy control subjects using a video-based eye tracker. Results The lesion comprised the FOR bilaterally but spared the posterior vermis. The initial pursuit acceleration was low but not significantly different from the healthy control subjects and sinusoidal pursuit was normal. Bilateral saccade hypermetria was not only seen with visually-guided saccades but also anti-saccades and memory-guided saccades. Final eye position remained accurate. Conclusions We provide new insights into the contribution of the bilateral deep cerebellar nuclei on the initial acceleration of human smooth pursuit in midline cerebellar lesions. In line with experimental bilateral FOR lesion data in non-human primates, the initial pursuit acceleration in our patient was not significantly reduced, in contrast to effects of unilateral experimental FOR lesions. Working memory and neural representation of target locations seem to remain unimpaired. Our data argue against an impaired common command feeding the circuits controlling saccadic and pursuit eye movements and support the hypothesis of independent influences on the neural processes generating both types of eye movements in the deep cerebellar nuclei .